Evaluation on toxicity level of Terminalia catappa leaves extract on selected cyprinids under different bath concentrations - Hashim, Emi Fazlina; John, Irence; A Ghani, Intan Faraha; Azmai, Mohammad Noor Amal (Universiti Putra Malaysia Press, 2020)
This study aimed to determine the lethal concentration (LC50) of Terminalia catappa leaves extract on three cyprinid species; carp (Cyprinus carpio), goldfish (Carassius auratus) and tiger barb (Puntigrus tetrazona) through the acute toxicity test. The leaves of T. catappa were extracted with methanol and prepared in various immersion concentrations (40, 80, 100, 150, 200, 250, 300, and 350 mg/L). These extracts were immersed in the aquarium and left for 24 h before performing the acute toxicity test. The water quality was also analyzed before and after adding the extract immersions into the aquarium. The acute toxicity test conducted for 96 h with 10 fishes of each cyprinid species (4.0-6.0 cm length) in 30 L water capacity aquarium. The mortality of each cyprinid species was recorded at 24 h time interval and LC50 of the extracts throughout 96 hours was determined through the probit analysis application. Specifically, the LC50 of T. catappa leaves extract were 349.89, 338.65 and 318.48 mg/L exhibited for carp, goldfish and tiger barb, respectively. A high concentration range of any plant-based extract has the potential to become toxic to particular fishes. Thus, it is an effort from this study to identify the safety margin of T. catappa leaves extract before its therapeutic values can be further manipulated and elucidated in aquaculture research.